Optimization of peotien determination using design of experiment (DOE) on earthworm powder - Siti Nursheela Abu Mansor (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2010)
The chemical compositions of the earthworm Eisenia foetida, its casts and body fluids were investigated and compared with those of a variety of common foods and animal feeds. Nutrient analyses showed that Eisenia foetida meal has high protein content in the range of 54.6 to 76.0% dry matter.